Pembelajaran IPA SD Menurut Perspektif Islam - Nurfadilah, Arini Nur; Julia, Ajeng; Trisnawati, Riska; Fitriani, Widya Ningrum; Fajrussalam, Hisny (Ikhtisar: Jurnal Pengetahuan Islam, 2022)
The existence of Islamic religious education in each educational unit has the aim of improving the soul and spiritual attitude and character formation of students, namely so that they can become human beings who believe and fear Allah S.W.T. Regarding matters of faith and piety, this can be applied in learning in schools such as in science learning in elementary schools regarding environmental awareness. In the world of education, environmental awareness is not an easy thing to do, but in Islam, humans must be able to protect the environment as well as possible because it is a form of our gratitude to the creator. Based on this, we used the literature review method in gathering information for this article, such as literature review of journals, books, papers, and articles. The results of this mini research show that based on Q.s Al-Baqarah: 22 the earth as a stretch and the sky as its roof, then the wind brings good news that there are clouds that are heading to a barren area. Then it rains giving water to living things and living things can benefit each other.